2006
DOI: 10.1248/bpb.29.1175
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of .GAMMA.-Tocopherol Derivative Prevents UV-Induced Skin Pigmentation

Abstract: Melanin plays an important role in preventing ultraviolet (UV) light-induced skin damage. On the other hand, overexposure to UV radiation can lead to a pathological increase in melanin production. Epidermal hyper-pigmentation results from the increased activity of melanogenic enzymes such as tyrosinase. [1][2][3] Tyrosinase oxidizes the conversion of L-tyrosine to 3,4-dihydroxyphenylalanine (DOPA) and DOPA to DOPA quinone, which are the first two rate limiting steps in the melanin synthesis pathway. 3,4) As su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…A direct effect of UV photons on DNA results in upregulation of the gene for tyrosinase, this then leading to epidermal hyper-pigmentation. [1][2][3] Tyrosinase oxidizes the conversion of L-tyrosine to 3,4-dihydroxyphenylalanine (DOPA) and of DOPA to DOPA quinone, these being the first two rate-limiting steps on the melanin synthesis pathway. 2,4) UV radiation also induces the formation of reactive oxygen species (ROS) in the skin; these ROS contribute to melanin biosynthesis and DNA damage and may then induce the proliferation and/or apoptosis of melanocytes.…”
mentioning
confidence: 99%
“…A direct effect of UV photons on DNA results in upregulation of the gene for tyrosinase, this then leading to epidermal hyper-pigmentation. [1][2][3] Tyrosinase oxidizes the conversion of L-tyrosine to 3,4-dihydroxyphenylalanine (DOPA) and of DOPA to DOPA quinone, these being the first two rate-limiting steps on the melanin synthesis pathway. 2,4) UV radiation also induces the formation of reactive oxygen species (ROS) in the skin; these ROS contribute to melanin biosynthesis and DNA damage and may then induce the proliferation and/or apoptosis of melanocytes.…”
mentioning
confidence: 99%
“…It was found that Red Ginseng extract (20 or 60 mg/kg, twice daily) prevented increased production of melanin. It has been reported that ascorbic acid derivatives and γ-tocopherol derivatives decreased UVB-induced skin hyper-pigmentation and melanin levels through their antioxidative properties (Kuwabara et al, 2006;Ochiai et al, 2006). Im et al (2003) reported that Ginseng radix inhibited tyrosinase activity and decreased melanin content and cell proliferation in B16 melanoma cells (in vitro).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophilic γ-tocotrienol reduced UV-induced pigmentation in guinea pig skin via inhibition of tyrosinase activity (Kuwabara et al, 2006). Tocotrienols inhibited UVB-induced melanogenesis in different melanoma cells through downregulation of tyrosinase activity and protein (Yap et al, 2010).…”
Section: Natural Antioxidants Antimelanogenic Actionsmentioning
confidence: 95%